Preparation method of methyl mercaptan degradation catalyst, methyl mercaptan degradation catalyst and application of methyl mercaptan degradation catalyst
Through the combination of lanthanum and copper doped mesoporous titanium dioxide catalyst and plasma technology, the problems of low degradation efficiency of plasma treatment and expensive catalysts are solved, and efficient and economical degradation effect of methyl mercaptan is achieved.
Patent Information
- Application Number
- CN202411362501.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The degradation efficiency of existing plasma-treated methylmercaptans is limited and the energy utilization rate is low. The catalyst designed by the existing plasma cocatalyst is expensive and has a small processing volume, making it difficult to meet economic needs.
The high-performance catalyst is prepared by doping mesoporous titanium dioxide with lanthanum and copper. Combined with the dielectric barrier discharge plasma technology, the foul-odor gas methylmercaptan is coordinated. The preparation methods include concentrated hydrochloric acid, deionized water, anhydrous ethanol, and titanium acid. The combination of tetrabutyl ester, template agent, copper source and lanthanum source is used to form a composite doping catalyst to improve the activity and specific surface area of the catalyst.
The degradation rate of methylmercaptan was significantly improved, from 45-55% to 80.2-89.2%, and the cost of the catalyst was reduced, achieving efficient foul-odor gas treatment.
Smart Images

Figure CN119236955A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of plasma catalytic degradation of malodorous gases, and in particular to a preparation method of a methyl mercaptan degradation catalyst, a methyl mercaptan degradation catalyst and applications thereof. Background Art
[0002] With economic development and social progress, odor pollution has gradually become a focus of people's attention, and the control of odor pollution has become an urgent problem to be solved. According to reports, the causes and sources of odor pollution are complex, and the main components of odorous gases include methyl mercaptan, methyl sulfide, ammonia and hydrogen sulfide. Methyl mercaptan has a low olfactory threshold and can produce a heavier odor at a lower concentration, making it difficult to control.
[0003] At present, there are related studies, such as Yi Rongjie et al., Research Status and Prospects of Methyl Mercaptan Odor Gas Treatment Technology, Journal of Jiangsu University, November 2022, Vol. 43, No. 6; This paper introduces the research status of commonly used methyl mercaptan treatment technologies at home and abroad, focusing on the emerging popular methyl mercaptan treatment technologies such as catalytic decomposition, catalytic oxidation, photocatalytic oxidation and low-temperature plasma in recent years, and points out their respective scope of application and advantages and disadvantages; The results show that catalytic decomposition, catalytic oxidation and photocatalytic oxidation have the advantages of high treatment efficiency, good adaptability and low product harm, but there are also problems such as poor catalyst activity and stability; Low-temperature plasma method is efficient and flexible, but it has the disadvantages of low energy utilization and easy production of toxic by-products; In the case that a single treatment process is difficult to meet the economic requirements, in order to efficiently treat methyl mercaptan, multiple treatment processes should be used in coordination, and the degradation mechanism needs to be further explored.
[0004] Plasma method is widely concerned due to its advantages such as easy start and stop, simple equipment and good treatment effect. However, plasma treatment of methyl mercaptan alone has disadvantages such as limited degradation efficiency and low energy utilization. In order to solve these problems, the synergistic effect of catalyst and plasma is becoming a research hotspot. The catalyst designed by the existing plasma synergistic catalyst technology is expensive and has a small processing capacity, so the development of economical and efficient catalysts is of great application value. Summary of the invention
[0005] In view of the problems in the prior art of treating methyl mercaptan with plasma alone, such as limited degradation efficiency and low energy utilization, and the expensive catalyst designed by plasma synergistic catalyst technology and small processing capacity, the present invention provides a method for preparing a methyl mercaptan degradation catalyst and a methyl mercaptan degradation catalyst and application thereof, which are used for plasma catalytic degradation of malodorous gases.
[0006] To achieve the above object, the present invention provides a method for preparing a methyl mercaptan degradation catalyst, comprising the following steps:
[0007] S1, mixing concentrated hydrochloric acid, deionized water and anhydrous ethanol and stirring to obtain a reaction solution A, wherein the volume ratio of concentrated hydrochloric acid, deionized water and anhydrous ethanol is (1-3):2:10;
[0008] S2, adding tetrabutyl titanate to the reaction solution A and heating, the volume ratio of tetrabutyl titanate to the reaction solution A is (1-2): (3-6), the heating temperature is 50-60° C., the heating time is 2-4 h, and after the heating is completed, cooling to room temperature to obtain a reaction solution B;
[0009] S3, adding a template to the reaction solution B and stirring to dissolve, then adding a copper source and a lanthanum source, wherein the molar ratio of the copper source to the lanthanum source is (1-3):(0.1-1), to obtain a reaction solution C;
[0010] The template agent is polyethylene glycol 2000, and the mass ratio of the template agent to tetrabutyl titanate is (1-2):(3-5);
[0011] The copper source is one or more of copper nitrate, acetic acid or copper sulfate, which can be mixed in any proportion; the lanthanum source is one or more of lanthanum nitrate, lanthanum acetate or lanthanum sulfate, which can be mixed in any proportion;
[0012] S4, while keeping the reaction solution C under stirring, add concentrated aqueous ammonia, the volume ratio of concentrated aqueous ammonia to reaction solution C is (1-3):(2-4), to obtain a paste;
[0013] S5, drying and calcining the obtained paste at a calcination temperature of 550-650°C, a calcination time of 5-7h, and a heating rate of 2-3°C / h to obtain a composite doped TiO2 catalyst, and the degradation rate of methyl mercaptan is increased to 80.2-89.2%.
[0014] In step S1, concentrated hydrochloric acid and water are used to adjust the pH. If the pH is too low, the solution cannot gel. Anhydrous ethanol is used as the reaction solvent.
[0015] In step S2, tetrabutyl titanate is used as a titanium source.
[0016] In step S3, the template agent polyethylene glycol 2000 is a porous material used to provide a porous environment for titanium dioxide.
[0017] In step S3, the ratio of the amount of copper source to the amount of lanthanum source is (1-3): (0.1-1). The bimetallic composite doping promotes the activation of the catalyst. The presence of lanthanum is to activate the catalyst. The oxygen vacancies that can be obtained by copper doping alone, too much copper will also cause copper oxide to aggregate, so that the specific surface area of the catalyst material is reduced. The introduction of lanthanum can make the material have more oxygen vacancies and also produce a larger specific surface area. However, the introduction of lanthanum is also limited, and too much lanthanum will not produce more oxygen vacancies. Therefore, it is necessary to control the ratio of the amount of copper source to the amount of lanthanum source to (1-3): (0.1-1).
[0018] Preferably, in step S5, the drying temperature is 65-85°C and the drying time is 24-48h; calcination is the process of removing the template, and too long heating time will lead to energy waste, while too short heating time will result in incomplete removal of the template.
[0019] To achieve the above object, the present invention also relates to a methyl mercaptan degradation catalyst, which is prepared by the above-mentioned preparation method of the methyl mercaptan degradation catalyst, and the methyl mercaptan degradation catalyst has the following technical indicators:
[0020] The methyl mercaptan degradation catalyst has the following technical indicators, including active components, carriers, preparation methods and application effects:
[0021] (1) Active components: The active components are Cu and La, which can provide more active sites and promote the generation of active oxygen, thereby enhancing the catalyst's ability to degrade methyl mercaptan;
[0022] (2) Carrier: The catalyst carrier is mesoporous titanium dioxide, which can increase the specific surface area of the catalyst, facilitate the dispersion of active components, and thus improve the activity of the catalyst;
[0023] (3) Preparation method: The preparation method of the catalyst adopts a co-condensation method and uses a simple and economical template agent to prepare mesoporous titanium dioxide;
[0024] (4) Application effect: The application effect of the catalyst is mainly reflected in the efficient degradation of methyl mercaptan.
[0025] In summary, the technical indicators of the methyl mercaptan degradation catalyst involve the selection of active components, the characteristics of the carrier, the optimization of the preparation method and the evaluation of the application effect. These factors jointly determine the performance of the catalyst and the efficiency of methyl mercaptan degradation, and the degradation rate of methyl mercaptan is increased from 45-55% to 80.2-89.2%.
[0026] To achieve the above object, the present invention also proposes a method for the degradation of mercaptan by using plasma and a methyl mercaptan degradation catalyst to synergistically degrade methyl mercaptan; specifically, the method comprises:
[0027] The raw material gas is introduced into a plasma reactor for degradation reaction, the discharge length of the plasma reactor is 10-100 mm, the power of the plasma reactor is 15-50 W, the duty cycle is 0-100%, and the modulation frequency is 10-500 Hz;
[0028] The raw gas includes methyl mercaptan and air, and the ratio of methyl mercaptan to air is 10 -6 -10 -5 , the flow rate of the raw gas is 100mL / min;
[0029] The above-mentioned methyl mercaptan degradation catalyst is arranged behind the discharge area of the plasma reactor, and the mass of the catalyst is 50-500 mg.
[0030] Compared with the prior art, the present invention has the following advantages:
[0031] The invention discloses a method for preparing a methyl mercaptan degradation catalyst, which utilizes lanthanum and copper elements to dope mesoporous titanium dioxide to prepare a high-performance catalyst, and uses dielectric barrier discharge plasma technology to treat the odorous gas methyl mercaptan, thereby providing a new method and new catalyst for methyl mercaptan degradation. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0033] Figure 1 Graph showing the degradation rate of methyl mercaptan under different input voltage dielectric barrier discharge plasma for different catalysts in Examples 1, 2 and 3 of the present invention;
[0034] Figure 2 The degradation rate diagram of methyl mercaptan of the catalyst in the comparative example of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In addition, the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0037] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings.
[0038] Embodiment 1:
[0039] A method for preparing a methyl mercaptan degradation catalyst comprises the following steps:
[0040] S1. Measure 3 mL of concentrated hydrochloric acid, 6 mL of deionized water, and 30 mL of anhydrous ethanol, pour them into a beaker and mix them, and stir them magnetically for 5 minutes;
[0041] S2, adding 10 mL 1 g / ml tetrabutyl titanate to the mixed solution obtained in step S1, stirring and reflux at 55° C. for 3 h;
[0042] S3, cooling the solution obtained in step S2 to room temperature, then adding 3 g of polyethylene glycol 2000, 0.276 g of copper nitrate and 0.2 g of lanthanum nitrate, while keeping the solution under stirring, adding 20 mL of concentrated ammonia water to obtain a light blue gel;
[0043] S4, drying the paste obtained in step S3 in an oven at 65°C to obtain a block structure;
[0044] S5. The block structure obtained in step S4 is calcined in a muffle furnace at 550° C. for 5 h with a heating rate of 2° C. / h, and finally a TiO2 catalyst 3% Cu-La / TiO2 doped with 3% Cu by mass and La:Cu=1:2 is obtained.
[0045] Take the catalyst 100mg obtained in Example 1, and place it in a homemade discharge plasma generator rear end catalyst filling tube, the filling tube inner diameter is about 10mm, the reactor inner diameter is about 24mm, the length is 250mm, the wall thickness is a quartz tube of 1.5mm, and the quartz tube center is provided with a discharge electrode, and a 0.1mm thick stainless steel mesh is wound around its surface as a ground electrode. The concentration of methyl mercaptan at the air inlet and outlet end of the discharge plasma generator is continuously detected under the working conditions of 20 ℃ of room temperature with a portable gas detector, and the concentration of methyl mercaptan at the air inlet and outlet end of the discharge plasma is also the concentration before and after the degradation of methyl mercaptan, and the degradation rate of methyl mercaptan can be obtained by calculating the concentration before and after the degradation of methyl mercaptan. Wherein the reaction gas composition is: methyl mercaptan and air.
[0046] Degradation of methyl mercaptan: the concentration of methyl mercaptan was 5 ppm, the flow rate of the reaction gas was 100 mL / min, and the applied voltage was 20-60 V.
[0047] from Figure 1 It can be seen that the 3Cu-La / TiO2 catalyst obtained in Example 1 has a degradation rate of methyl mercaptan from 45.0% to 84.2% when the applied voltage is between 20V and 60V, and has a good degradation effect on methyl mercaptan.
[0048] In contrast, under the condition of single doping of Cu catalyst, the applied voltage is between 20V and 60V, and the degradation rate of methyl mercaptan is increased from 40% to 79%. The degradation rate of the composite metal doped catalyst is significantly higher than that of the single metal doped catalyst. It can be seen that the catalyst of the present application has a better degradation effect on methyl mercaptan under the condition of synergistic discharge plasma, and it can be seen that the synergistic effect of this catalyst is better.
[0049] Embodiment 2:
[0050] A method for preparing a methyl mercaptan degradation catalyst comprises the following steps:
[0051] S1. Measure 3 mL of concentrated hydrochloric acid, 6 mL of deionized water, and 30 mL of anhydrous ethanol, pour them into a beaker and mix them, and stir them magnetically for 5 minutes;
[0052] S2, adding 10 mL of tetrabutyl titanate to the mixed solution obtained in step S1, and stirring and refluxing at 55° C. for 3 h;
[0053] S3, cooling the solution obtained in step S2 to room temperature, then adding 3 g of polyethylene glycol 2000, 0.470 g of copper nitrate and 0.3 g of lanthanum nitrate, while keeping the solution under stirring, adding 20 mL of concentrated ammonia water to obtain a blue gel;
[0054] S4, drying the paste obtained in step S3 in an oven at 65°C to obtain a block structure;
[0055] S5. The block structure obtained in step S4 is calcined in a muffle furnace at 550° C. for 5 h with a heating rate of 2° C. / h, and finally a 5% Cu-doped TiO2 catalyst 5Cu-La / TiO2 is obtained.
[0056] Take 100mg of the catalyst obtained in Example 2 and place it in a homemade discharge plasma generator rear end catalyst filling tube, the filling tube inner diameter is about 10mm, the reactor inner diameter is about 24mm, the length is 250mm, the wall thickness is 1.5mm quartz tube, the discharge electrode is arranged in the center of the quartz tube, and a 0.1mm thick stainless steel mesh is wound around its surface as a ground electrode. The concentration of methyl mercaptan at the air inlet and outlet of the discharge plasma generator is continuously detected with a portable gas detector under the working condition of room temperature 20°C. The concentration of methyl mercaptan at the air inlet and outlet of the discharge plasma is also the concentration before and after the degradation of methyl mercaptan. The degradation rate of methyl mercaptan can be obtained by calculating the concentration before and after the degradation of methyl mercaptan. Wherein the reaction gas composition is:
[0057] Degradation of methyl mercaptan: the concentration of methyl mercaptan was 5 ppm, the flow rate of the reaction gas was 100 mL / min, and the applied voltage was 20-60 V.
[0058] from Figure 1 It can be seen that the 5Cu-La / TiO2 catalyst obtained in Example 2 has a degradation rate of methyl mercaptan from 55.0% to 89.2% when the applied voltage is between 20V and 60V, and has a good degradation effect on methyl mercaptan.
[0059] Under the condition of Cu catalyst doping alone, the applied voltage is between 20V and 60V, and the degradation rate of methyl mercaptan is increased from 45% to 84%. The degradation rate of the composite metal doped catalyst is significantly higher than that of the single metal doped catalyst. It can be seen that the catalyst has a better degradation effect on methyl mercaptan under the condition of synergistic discharge plasma, and it can also be seen that the synergistic effect of this catalyst is better.
[0060] Embodiment 3:
[0061] A method for preparing a methyl mercaptan degradation catalyst comprises the following steps:
[0062] S1. Measure 3 mL of concentrated hydrochloric acid, 6 mL of deionized water, and 30 mL of anhydrous ethanol, pour them into a beaker and mix them, and stir them magnetically for 5 minutes;
[0063] S2, adding 10 mL of tetrabutyl titanate to the mixed solution obtained in step S1, and stirring and refluxing at 55° C. for 3 h;
[0064] S3, cooling the solution obtained in step S2 to room temperature, then adding 3 g of polyethylene glycol 2000, 0.672 g of copper nitrate and 0.48 g of lanthanum nitrate, keeping the solution under stirring, adding 20 mL of concentrated ammonia water to obtain a blue gel;
[0065] S4, drying the paste obtained in step S3 in an oven at 65°C to obtain a block structure;
[0066] S5. The block structure obtained in step S4 is calcined in a muffle furnace at 550° C. for 5 h with a heating rate of 2° C. / h, and finally a TiO2 catalyst 7Cu-La / TiO2 doped with 7% Cu is obtained.
[0067] Take 100mg of the catalyst obtained in Example 3 and place it in a homemade discharge plasma generator rear end catalyst filling tube, the filling tube inner diameter is about 10mm, the reactor inner diameter is about 24mm, the length is 250mm, the wall thickness is 1.5mm quartz tube, the discharge electrode is arranged in the center of the quartz tube, and a 0.1mm thick stainless steel mesh is wound around its surface as a ground electrode. The concentration of methyl mercaptan at the air inlet and outlet of the discharge plasma generator is continuously detected under the working condition of room temperature 20°C using a portable gas detector. The concentration of methyl mercaptan at the air inlet and outlet of the discharge plasma is also the concentration before and after the degradation of methyl mercaptan. The degradation rate of methyl mercaptan can be obtained by calculating the concentration before and after the degradation of methyl mercaptan. Wherein the reaction gas composition is:
[0068] Degradation of methyl mercaptan: the concentration of methyl mercaptan was 5 ppm, the flow rate of the reaction gas was 100 mL / min, and the applied voltage was 20-60 V.
[0069] from Figure 1 It can be seen that the 7Cu-La / TiO2 catalyst obtained in Example 3 has a degradation rate of methyl mercaptan from 45.5% to 80.2% when the applied voltage is between 20V and 60V, and has a good degradation effect on methyl mercaptan.
[0070] Under the condition of Cu catalyst doping alone, the applied voltage is between 20V and 60V, and the degradation rate of methyl mercaptan is increased from 40% to 79%. The degradation rate of the composite metal doped catalyst is significantly higher than that of the single metal doped catalyst. It can be seen that the catalyst has a better degradation effect on methyl mercaptan under the condition of synergistic discharge plasma, and it can also be seen that the synergistic effect of this catalyst is better.
[0071] Example 3 After the 7Cu-La / TiO2 catalyst was placed for 72 hours, the degradation rate of methyl mercaptan at an applied voltage of 40V was as follows: Figure 1 As shown, it can still reach 60%, with good stability.
[0072] Comparative Example 1:
[0073] The difference between Comparative Example 1 and Example 1 is that the catalyst in Comparative Example 1 is not doped with lanthanum, that is, the amount of copper is equal to the sum of the amounts of copper and lanthanum in Example 1, and the steps are as follows:
[0074] S1. Measure 3 mL of concentrated hydrochloric acid, 6 mL of deionized water, and 30 mL of anhydrous ethanol, pour them into a beaker and mix them, and stir them magnetically for 5 minutes;
[0075] S2, adding 10 mL of tetrabutyl titanate to the mixed solution obtained in step S1, and stirring and refluxing at 55° C. for 3 h;
[0076] S3, cooling the solution obtained in step S2 to room temperature, then adding 3 g of polyethylene glycol 2000 and 0.414 g of copper nitrate, keeping the solution under stirring, and adding 20 mL of concentrated ammonia water to obtain a blue gel;
[0077] S4, drying the paste obtained in step S3 in an oven at 65°C to obtain a block structure;
[0078] S5. The block structure obtained in step S4 is calcined in a muffle furnace at 550° C. for 5 h at a heating rate of 2° C. / h to obtain.
[0079] Take 100mg of the catalyst obtained in Comparative Example 1 and place it in a catalyst filling tube at the rear end of a homemade discharge plasma generator. The filling tube has an inner diameter of about 10mm, a reactor inner diameter of about 24mm, a length of 250mm, and a wall thickness of 1.5mm. A discharge electrode is arranged in the center of the quartz tube, and a 0.1mm thick stainless steel mesh is wound around its surface as a ground electrode. The concentration of methyl mercaptan at the inlet and outlet of the discharge plasma generator is continuously detected by a portable gas detector under a room temperature of 20°C. The concentration of methyl mercaptan at the inlet and outlet of the discharge plasma is also the concentration of methyl mercaptan before and after degradation. The degradation rate of methyl mercaptan can be obtained by calculating the concentration before and after degradation of methyl mercaptan. The reaction gas composition is:
[0080] Degradation of methyl mercaptan: the concentration of methyl mercaptan was 5 ppm, the flow rate of the reaction gas was 100 mL / min, and the applied voltage was 20-60 V.
[0081] from Figure 2 It can be seen that the Cu / TiO2 catalyst obtained in Comparative Example 1 has a degradation rate for methyl mercaptan increased from 40% to 79% when the applied voltage is between 20V and 60V, and has a degradation effect on methyl mercaptan.
[0082] Under the condition of La and Cu bimetallic doping, the applied voltage is between 20V and 60V, and the degradation rate of methyl mercaptan is increased from 45% to 84.2%. The degradation rate of the bimetallic catalyst is significantly higher than that of the single metal degradation. It can be seen that the catalyst has a better degradation effect on methyl mercaptan in the case of synergistic discharge plasma, and it can also be seen that the synergistic effect of this catalyst is better.
[0083] Comparative Example 2:
[0084] The difference between Comparative Example 2 and Example 1 is that the metal doping amount remains unchanged, and the ratio of Cu to La is increased, and the following steps are included:
[0085] S1. Measure 3 mL of concentrated hydrochloric acid, 6 mL of deionized water, and 30 mL of anhydrous ethanol, pour them into a beaker and mix them, and stir them magnetically for 5 minutes;
[0086] S2, adding 10 mL of tetrabutyl titanate to the mixed solution obtained in step S1, and stirring and refluxing at 55° C. for 3 h;
[0087] S3, cooling the solution obtained in step S2 to room temperature, then adding 3 g of polyethylene glycol 2000, 0.276 g of copper nitrate and 0.17 g of lanthanum nitrate, keeping the solution under stirring, adding 20 mL of concentrated ammonia water to obtain a blue gel;
[0088] S4, drying the paste obtained in step S3 in an oven at 65°C to obtain a block structure;
[0089] S5. The block structure obtained in step S4 is calcined in a muffle furnace at 550° C. for 5 h with a heating rate of 2° C. / h, and finally a TiO2 catalyst 3Cu1La / TiO2 doped with Cu:La=3:1 is obtained.
[0090] Take 100mg of the catalyst obtained in Comparative Example 2 and place it in a homemade discharge plasma generator rear end catalyst filling tube, the filling tube inner diameter is about 10mm, the reactor inner diameter is about 24mm, the length is 250mm, the wall thickness is 1.5mm quartz tube, the discharge electrode is arranged in the center of the quartz tube, and a 0.1mm thick stainless steel mesh is wound around its surface as a ground electrode. Use a portable gas detector to continuously detect the concentration of methyl mercaptan at the air inlet and outlet of the discharge plasma generator under the working condition of room temperature 20°C. The concentration of methyl mercaptan at the air inlet and outlet of the discharge plasma is also the concentration before and after the degradation of methyl mercaptan. The degradation rate of methyl mercaptan can be obtained by calculating the concentration before and after the degradation of methyl mercaptan. Wherein the reaction gas composition is:
[0091] Degradation of methyl mercaptan: the concentration of methyl mercaptan was 5 ppm, the flow rate of the reaction gas was 100 mL / min, and the applied voltage was 20-60 V.
[0092] from Figure 2 It can be seen that the 9Cu1La / TiO2 catalyst obtained in Comparative Example 2 has a degradation rate of methyl mercaptan from 42.5% to 80% when the applied voltage is between 20V and 60V, and has a degradation effect on methyl mercaptan.
[0093] Under normal bimetallic conditions, the applied voltage is between 20V and 60V, and the degradation rate of methyl mercaptan is increased from 45% to 84.2%. In the case of bimetallic catalyst and normal doping amount, the degradation rate is significantly higher than that of inappropriate metal doping ratio. It can be seen that the catalyst has a better degradation effect on methyl mercaptan in the case of synergistic discharge plasma, and it can also be seen that the synergistic effect of this catalyst is better.
[0094] Comparative Example 3:
[0095] The difference between Comparative Example 3 and Example 1 is that the total amount of metal doping remains unchanged, and the ratio of Cu and Lan elements is reduced, and the following steps are included:
[0096] S1. Measure 3 mL of concentrated hydrochloric acid, 6 mL of deionized water, and 30 mL of anhydrous ethanol, pour them into a beaker and mix them, and stir them magnetically for 5 minutes;
[0097] S2, adding 10 mL of tetrabutyl titanate to the mixed solution obtained in step S1, and stirring and refluxing at 55° C. for 3 h;
[0098] S3, cooling the solution obtained in step S2 to room temperature, then adding 3 g of polyethylene glycol 2000, 0.276 g of copper nitrate and 0.5 g of lanthanum nitrate, keeping the solution under stirring, adding 20 mL of concentrated ammonia water to obtain a blue gel;
[0099] S4, drying the paste obtained in step S3 in an oven at 65°C to obtain a block structure;
[0100] S5. The block structure obtained in step S4 is calcined in a muffle furnace at 550° C. for 5 h with a heating rate of 2° C. / h, and finally a Cu:La=1:1 element-doped TiO2 catalyst 1Cu1La / TiO2 is obtained.
[0101] Take 100mg of the catalyst obtained in Comparative Example 3 and place it in a homemade discharge plasma generator rear end catalyst filling tube, the filling tube inner diameter is about 10mm, the reactor inner diameter is about 24mm, the length is 250mm, the wall thickness is 1.5mm quartz tube, the discharge electrode is arranged in the center of the quartz tube, and a 0.1mm thick stainless steel mesh is wound around its surface as a ground electrode. Use a portable gas detector to continuously detect the concentration of methyl mercaptan at the air inlet and outlet of the discharge plasma generator under the working condition of room temperature 20°C. The concentration of methyl mercaptan at the air inlet and outlet of the discharge plasma is also the concentration of methyl mercaptan before and after degradation. The degradation rate of methyl mercaptan can be obtained by calculating the concentration before and after degradation of methyl mercaptan. The reaction gas composition is:
[0102] Degradation of methyl mercaptan: the concentration of methyl mercaptan was 5 ppm, the flow rate of the reaction gas was 100 mL / min, and the applied voltage was 20-60 V.
[0103] from Figure 2 It can be seen that the 1Cu-La / TiO2 catalyst obtained in Comparative Example 3 has a degradation rate of methyl mercaptan increased from 41% to 81% when the applied voltage is between 20V and 60V, and has a good degradation effect on methyl mercaptan.
[0104] Under normal bimetallic conditions, the applied voltage is between 20V and 60V, and the degradation rate of methyl mercaptan is increased from 45% to 84%. The degradation rate of the case with bimetallic catalyst and normal doping amount is significantly higher than the case of degradation when the ratio of the two is too low. It can be seen that the catalyst has a better degradation effect on methyl mercaptan in the case of synergistic discharge plasma, and it can also be seen that the synergistic effect of this catalyst is better.
[0105] Analysis and discussion:
[0106] 1. By comparing Examples 1-3 with Comparative Example 1, it can be seen that the catalyst in Comparative Example 1 is not doped with lanthanum, that is, the amount of copper is equal to the sum of the amounts of copper and lanthanum in Example 1. The Cu / TiO2 catalyst obtained in Comparative Example 1 increases the degradation rate of methyl mercaptan from 40% to 79%; the methyl mercaptan degradation catalyst of the present invention increases the degradation rate of methyl mercaptan from 45% to 84.2%, indicating that the degradation rate of the bimetallic catalyst is significantly higher than that of the monometallic degradation. It can be seen that the catalyst of the present invention has a better degradation effect on methyl mercaptan in the case of synergistic discharge plasma, and it can be seen that the synergistic effect of the catalyst is better.
[0107] 2. By comparing Examples 1-3 with Comparative Example 2, it can be seen that the amount of catalyst metal doping in Comparative Example 2 remains unchanged, the ratio of Cu and La increases, and the degradation rate of methyl mercaptan is increased from 42.5% to 80%; the methyl mercaptan degradation catalyst of the present invention increases the degradation rate of methyl mercaptan from 45% to 84.2%. In the case of a bimetallic catalyst and a normal doping amount, the degradation rate is significantly higher than that of an inappropriate degradation due to inappropriate metal doping ratio. It can be seen that the catalyst has a better degradation effect on methyl mercaptan in the case of a synergistic discharge plasma, and it can also be seen that the synergistic effect of the catalyst is better.
[0108] 3. By comparing Examples 1-3 and Comparative Example 3, it can be seen that the total amount of catalyst metal doping in Comparative Example 3 remains unchanged, the ratio of Cu and Lan elements is reduced, and the degradation rate of methyl mercaptan is increased from 41% to 81%; the methyl mercaptan degradation catalyst of the present invention increases the degradation rate of methyl mercaptan from 45% to 84%, and the degradation rate of the bimetallic catalyst and the normal doping amount is significantly higher than the degradation of the ratio of the two. It can be seen that the catalyst has a better degradation effect on methyl mercaptan in the case of synergistic discharge plasma, and it can be seen that the synergistic effect of the catalyst is better. The methyl mercaptan degradation catalyst of the present invention increases the degradation rate of methyl mercaptan from 45-55% to 80.2-89.2%.
[0109] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. Therefore, the scope of protection of the present invention should be subject to the scope of protection of the claims.
Claims
1. A method for preparing a methyl mercaptan degradation catalyst, characterized in that: The following steps are involved: S1, mixing concentrated hydrochloric acid, deionized water and anhydrous ethanol and stirring to obtain a reaction solution A, wherein the volume ratio of concentrated hydrochloric acid, deionized water and anhydrous ethanol is (1-3):2:10; S2, adding tetrabutyl titanate to the reaction solution A and heating, the volume ratio of tetrabutyl titanate to the reaction solution A is (1-2): (3-6), the heating temperature is 50-60° C., the heating time is 2-4 h, and after the heating is completed, cooling to room temperature to obtain a reaction solution B; S3, adding a template to the reaction solution B and stirring to dissolve, then adding a copper source and a lanthanum source, wherein the molar ratio of the copper source to the lanthanum source is (1-3):(0.1-1), to obtain a reaction solution C; The template agent is polyethylene glycol 2000, and the mass ratio of the template agent to tetrabutyl titanate is (1-2):(3-5); The copper source is one or more of copper nitrate, acetic acid or copper sulfate, which can be mixed in any proportion; the lanthanum source is one or more of lanthanum nitrate, lanthanum acetate or lanthanum sulfate, which can be mixed in any proportion; S4, while keeping the reaction solution C under stirring, add concentrated aqueous ammonia, the volume ratio of concentrated aqueous ammonia to reaction solution C is (1-3):(2-4), to obtain a paste; S5. Drying and calcining the obtained paste at a temperature of 550-650° C. for 5-7 h at a heating rate of 2-3° C. / h to obtain a composite-doped TiO2 catalyst with a degradation rate of 80.2-89.2% for methyl mercaptan.
2. The method for preparing a methyl mercaptan degradation catalyst according to claim 1, wherein: In step S5, the drying temperature is 65-85°C and the drying time is 24-48 hours.
3. A methyl mercaptan degradation catalyst, characterized in that: The catalyst is prepared by the method for preparing a methyl mercaptan degradation catalyst according to claim 1 or 2. The methyl mercaptan degradation catalyst has the following technical indicators: the degradation rate of methyl mercaptan is 80.2-89.2%.
4. An application of a mercaptan degradation catalyst, characterized in that: The synergistic degradation of methyl mercaptan using plasma and methyl mercaptan degradation catalyst specifically includes: The raw material gas is introduced into a plasma reactor for degradation reaction, the discharge length of the plasma reactor is 10-100 mm, the power of the plasma reactor is 15-50 W, the duty cycle is 0-100%, and the modulation frequency is 10-500 Hz; The raw gas includes methyl mercaptan and air, and the ratio of methyl mercaptan to air is 10 -6 -10 -5 , the flow rate of the raw gas is 100mL / min; The methyl mercaptan degradation catalyst according to claim 3 is arranged behind the discharge area of the plasma reactor, and the mass of the catalyst is 50-500 mg.
